The scorecard solution : measure what matters and drive sustainable growth - King, Dan E. (American Management Association, 2015)
Simply "making the numbers" is no longer enough to remain competitive. In today's high-pressure environment, organizations need to overachieve. That level of success requires a clear and objective view of the business--because even the most courageous leader can't steer a ship in the dark. Is the enterprise agile, resilient, vulnerable or lagging? This book introduces a data-centric tool--the Organizational Prowess Scorecard--that precisely measures the capabilities needed for sustainable growth. Analyzing the dimensions of talent, strategy, and execution produces a baseline score, and shines a light on the performance gaps that hold a business back. With the facts in hand, readers then learn how to: position the organization to meet ambitious goals; bring strategies to life through an execution framework; design a dashboard to track progress and flag problems; and foster a winning culture. --